Effectiveness of fungicides at different stages of development of maize maternallinesandtheirimpactonyield - Koba, K.; Marenych, M. (Scientific Progress & Innovations, 2024)
Maize is one of the most widely cultivated cereal crops in the world. Consequently, the productivity of its maternal lines plays a crucial role in ensuring the stability and quality of hybrid seeds. This study investigates the efficacy of fungicides applied at different growth stages of maize maternal lines and their direct impact on yield. The main objective of the research was to identify optimal strategies for protecting maternal lines from fungal infections to enhance their productivity.Experiments conducted in the Central Forest-Steppe region of Ukraine evaluated the efficacy of three fungicides (Acanto Plus, Abacus, and Coronet) applied at different stages: the 8-leaf stage (V8/BBCH18), the tasseling stage (VT/BBCH63), and their combination (V8+VT). The results showed that the highest yield was achieved with Abacus applied at the V8+VT stages (average yield — 5.01 t/ha), which was 25 % higher compared to the control. Combined application at the V8+VT stages demonstrated the highest effectiveness for all products, emphasizing the importance of protection at all stages of plant development. Analysis of variance (ANOVA) confirmed the significant impact of application stages (58 % of total variation) and fungicide type (42 %) on yield, while the interaction of these factors was negligible. Additionally, the results highlighted the substantial influence of weather conditions across different years on fungicide efficacy, indicating the necessity of adapting protection technologies to specific climatic conditions. Further analysis indicates that weather stresses such as drought or excessive moisture can alter the response of plants to fungicide treatments. This highlights the importance of monitoring weather conditions to ensure timely application. The obtained data provide practical insights for improving the protection system of maize maternal lines, particularly in selecting fungicide application stages and products. This approach can significantly increase seed yield and quality while ensuring the efficient use of agronomic practices. Furthermore, the findings can be used to refine recommendations for sustainable hybrid maize seed production.